2023
DOI: 10.3390/allergies3010003
|View full text |Cite
|
Sign up to set email alerts
|

Seed Storage Protein, Functional Diversity and Association with Allergy

Abstract: Plants are essential for humans as they serve as a source of food, fuel, medicine, oils, and more. The major elements that are utilized for our needs exist in storage organs, such as seeds. These seeds are rich in proteins, show a broad spectrum of physiological roles, and are classified based on their sequence, structure, and conserved motifs. With the improvements to our knowledge of the basic sequence and our structural understanding, we have acquired better insights into seed proteins and their role. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 144 publications
0
4
0
Order By: Relevance
“…Particularly, the proteins able to bind to nutrients and important for nutrient accumulation during seed germination, for example, are usually also involved in host defense and provide resistance to disease. These include seed storage proteins 141 which include the large prolamin superfamily 142–144 comprised of lipid transfer proteins, 2S albumins, cereal prolamins, and the cupins consisting of globulins (legumin‐like proteins) and conglutins (vicilin‐like proteins) as well as pathogenesis‐related proteins 141 . From animal sources animal proteins such as albumins, lipocalins, transferrins, and globulins are similarly serving as carrier for nutrients binding to carbohydrates, 145 minerals, 146–159 lipids, 160–163 phenolics, 146,154–156 and vitamins 149–153 and often play a regulatory role in host defense.…”
Section: Dietary Absorption Of Nutrients: the Bioavailability Differs...mentioning
confidence: 99%
“…Particularly, the proteins able to bind to nutrients and important for nutrient accumulation during seed germination, for example, are usually also involved in host defense and provide resistance to disease. These include seed storage proteins 141 which include the large prolamin superfamily 142–144 comprised of lipid transfer proteins, 2S albumins, cereal prolamins, and the cupins consisting of globulins (legumin‐like proteins) and conglutins (vicilin‐like proteins) as well as pathogenesis‐related proteins 141 . From animal sources animal proteins such as albumins, lipocalins, transferrins, and globulins are similarly serving as carrier for nutrients binding to carbohydrates, 145 minerals, 146–159 lipids, 160–163 phenolics, 146,154–156 and vitamins 149–153 and often play a regulatory role in host defense.…”
Section: Dietary Absorption Of Nutrients: the Bioavailability Differs...mentioning
confidence: 99%
“…The cross-reactivities between fruit allergens and homologous proteins from other vegetable, seed, and pollen sources account for different food-pollen syndromes. The allergens responsible for these food-pollen syndromes essentially consist of the pan-allergens nsLTPs, profilins, GRPs, β-1,3-glucanases, but also the seed storage proteins [4]. Most often these pollen-food syndromes result in a benign oral allergy syndrome (OAS) but can, less frequently, lead to a more severe systemic reaction, especially with the peach nsLTP Pru p 3 [27,75].…”
Section: Cross-reactivity Of Fruit Allergensmentioning
confidence: 99%
“…In addition, a few allergens, including Cuc m 3 of the PR-1 family, bromelain (Ana c 2) and kiwelin (Act c 5), belong to a single fruit or a restricted number of fruits. Finally, proteins that belong to the three classes of seed storage proteins from higher plants, 2S albumins, 7S globulins (vicilin), and 11S globulins (legumin) [4], should also be retained as possible potential fruit allergens resulting from the unintended consumption of the seeds of kernels [5]. Many of these fruit allergens represent widely distributed pan-allergens, which are responsible for IgE-binding cross-reactivity often associated with some cross-allergenicity.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies demonstrated that rice SSPs modulate glutathione metabolism, mitigate oxidative damage to lipids and proteins, and provoke antioxidative responses against hypercholesterolemia, although glutelins appeared to be superior to prolamins as antioxidants [ 19 , 20 , 21 ]. Moreover, prolamins found in grains such as wheat, barley, and rye are known to cause allergic reactions such as celiac disease and IgE-mediated food allergies [ 22 , 23 , 24 ]. It is interesting that amino acid sequence analysis has revealed a close proximity between prolamins and protein allergens ( RA16/17 ) in rice seeds [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%